Echinacoside Protects Dopaminergic Neurons Through Regulating IL-6/JAK2/STAT3 Pathway in Parkinson’s Disease Model - Yang, Xueping; Yv, Qingyun; Ye, Fanlong; Chen, Sheng; He, Zhang; Li, Wenwei; Dong, Fang (Frontiers in Pharmacology, 2022)
Echinacoside (ECH), the major active constituent of Cistanche deserticola, was found to exert neuroprotection through neurotrophic and anti-inflammatory functions in Parkinson’s disease (PD) models; however, a clear intermediate molecule or pathway that unifies these two effects had yet to be found. In this study, our results demonstrated that ECH can protect DA neurons in PD mice with western blot and immunohistochemistry staining. Quantitative real-time polymerase chain reaction was adapted to confirm its anti-inflammatory function with decreased cytokines (interleukin (IL)-6, IL-1β and TNF-α) in PD mice and LPS induced BV2 cells. Further studies found that ECH inhibited the IL-6/JAK2/STAT3 pathway and decreased phosphorylation of STAT3 on tyr705 by western blot. It can also increase p-STAT3 (ser727) and brain derived neurotrophic factor (BDNF) expression in PD mice and LPS induced BV2 cells. This study revealed that ECH exerts neurotrophic and anti-inflammatory effects by regulating the IL-6/JAK2/STAT3 pathway and the phosphorylation of STAT3, promoting the mutually beneficial influence of the two effects to maximize its neuroprotective function.